PENINGKATAN KEMAMPUAN MENGAPRESIASI UNSUR INTRINSIK CERPEN MENGGUNAKAN METODE PEMBELAJARAN INKUIRI SISWA KELAS IX A SMP NEGERI 5 BIROMARU - Amiruddin Amiruddin (BAHASANTODEA, 2016)
Improving learning outcomes students is indication of  improving students competence the resulted of observation was in IX A SMP Negeri 5 Biromaru found that the learning outcomes of students did not achieve KKM, the average student achievement score is 57,4% from 25 students, there is a student that achieve score completeness or 4% the objective of this research described that the used of inquiry method for improving students competence and activity of  teaching learning process by the students and the teacher. This research applied qualitatif research through classroom action research (CAR). The researcher was helped by an indonesian teacher as a observer. It applied in SMP Negeri 5 Biromaru. The sample of this research was IX A ( first semester 2015/2016) which consisted of 25 students (16 female and 9 male students). Technique of data collections through worksheet, observation, student journal and interview. The resulted of using inquiry method is able to improve students competence in apreciation of  intrinstic elements of short story. Learning outcomes of student in cycle I (first meeting) 62,1 with enough category and (second meeting) 68,7 with enough category. So, the average score in cycle I is 62,1% with enough category. The learning outcomes in cycle II (first meeting) 71,6 with good category. And (second meeting) 82,9 with good category. So, the average score in cycle II is 77,3% with good category. The teaching learning process is good and fluent way. It is able to change students activities from less antusiasm into more antusiasm in teaching process.  It also effected to wake up student diligently and carefully to do an exercise. The teaching learning process that conducted by the teacher in cycle (I) is  68,8% with enough category and  in cycle (II) is 87,5% with very good category. It means the students improved until 17,7%. The teaching learning process that conducted by the students in cycle (I) is 62,5% and in cycle (II) is 81,3% with good category, it means the student improved until 18,8%. Keywords: Inquiry method, improving skills, intrinstic.